EDUKASI NARKOBA, HIV/AIDS, PORNOGRAFI DAN KESEHATAN REPRODUKSI REMAJA DI KELURAHAN BALAI GADANG KECAMATAN KOTO TANGAH KOTA PADANG - Syafrawati syafrawati; Ahmad Hidayat; Laila Isrona; Nadya Vebrielna (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
One of the adolescent deviant behavior that is rampant today is drug abuse. In addition, during adolescence, exploration of matters relating to sexuality begins. The search for information about sexual behavior is currently very much supported by technological advances, this has a negative impact in the form of easy access to pornography. Pornography can encourage teens to engage in sexual acts. It is important for adolescents to have knowledge related to reproductive health so as not to fall into free sex behavior that can lead to HIV/AIDS. The purpose of this activity is to provide education to adolescents related to drugs, pornography, reproductive health and HIV/AIDS to improve PHBS in adolescents and prevent adolescents from behavior that poses a risk to health. This activity was carried out on December 19, 2021 at the Nurul Yaqin Mosque, Balai Gadang Village. The target of this activity is 25 youths in Balai Gadang Village. The activity method is in the form of counseling which begins with preparations in the form of hearings with partners, setting a schedule of activities, speakers, and event materials. At the implementation stage, a pre-test was carried out, delivery of material on a predetermined topic and followed by a question and answer session. Then a post-test was conducted to determine the increase in adolescent knowledge. At the end of the session, health promotion media were distributed in the form of flyers to teenagers. The results of the activity showed that participants were enthusiastic in participating in the activity, there was even an increase in participants' knowledge of the material presented. Prior to health education (drugs, HIV/AIDS, pornography) the knowledge of participants was 53%, while after education the average knowledge was 65.2%. It is hoped that similar activities can be carried out to reduce deviant behavior in adolescents in Padang City.